Dystopia, surveillance and the spaces of social control in Jenni Fagan’s The Panopticon (2012) - Claire Wrobel (Sillages Critiques, 2022)
Although Jenni Fagan's The Panopticon (2012) does not qualify as a classic dystopia detailing a possible and undesirable future state of society, the novel shares some traits of the genre, including a protagonist struggling with a system against which she rebels. The dystopian space par excellence seems to be that delimited by the walls of the Panopticon, here an institution for young delinquents, which finds a counterpoint in the shape of an island utopia, a destination that becomes a symbol of harmony and freedom. However, panoptic space, contrary to what is asserted in the text, does not shelter the omnipresent and omniscient surveillance of which the Panopticon and Big Brother have become emblems. In contrast to the supposedly grid-like space of the Panopticon, readers find a literal space which is rich in nooks and crannies and a literary space which reveals an intertextual depth that draws, among other things, on a number of Gothic motifs. Although the text explicitly reappropriates the Panopticon designed by Jeremy Bentham (1748-1832), an invention itself riven by the tension between utopia and dystopia, and echoes Michel Foucault’s strategic reading in Discipline and Punish (1975), the virulent critique it levels at the welfare state echoes some of the central issues to be found in George Orwell's attack on totalitarian states, particularly those related to memory and language. The adoption of a first-person narrator allows Fagan to speak out against surveillance that consists in control only and to oppose dehumanizing institutional discourse.